Unlocking potential: evaluating the impact of training and development on staff performance in polytechnic Kuala Terengganu - Sharina Diana Johari, Sharina Diana Bt Johari; Ismail, Norhayati; A.Rahman, Nur Aimi (Southeast Asian Journal of Technology and Science, 2025)
The importance of training and development for organizations is crucial. This research aims to evaluate the effectiveness of training and development staff within the PKT organization. It explores how effective training and development can positively impact an organization and help achieve its goals. A group of 70 staff members participated in the survey-based study. The results showed that the majority of staff experienced improvements in knowledge, motivation, innovation, knowledge transfer, and confidence in teaching courses as a result of the training and development programs.The results show that there is a strong connection between specific training efforts and improved staff performance, emphasizing the significance of ongoing professional development. Moreover, the study identifies important elements that contribute to the effectiveness of training programs, such as being in line with the organization's objectives, engaging employees, and providing continuous support. The research ends by suggesting ways for organizations to improve their training and development strategies, ultimately unleashing their workforce's full potential and cultivating a culture of continual enhancement. Nevertheless, there are challenges such as cost, limited resources, and changes in technology, as well as potential solutions. It is anticipated that by using the results of this study and implementing several proposed plans, the organization will be able to maximize the benefits of training and development for their staff and achieve long-term objectives.